TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN INFORMASI OBAT DI APOTEK DOA BUNDA SENTANI KABUPATEN JAYAPURA - Nur Aida (Universitas Cokroaminoto Palopo, 2023)
Research has been carried out on the level of patient satisfaction with drug information services at the Doa Bunda Sentani Pharmacy. The purpose of this study was to determine the level of patient satisfaction in drug information services at the Doa Bunda Sentani Pharmacy, Jayapura Regency. The study was conducted by distributing questionnaires to 100 patients who came for treatment from April to June 2022. This type of research is descriptive by filling out questionnaires to visitors to the Doa Bunda Sentani pharmacy, Jayapura Regency. The results showed that the mean score for measuring the level of patient satisfaction with each measurement indicator, namely for responsiveness was 81.7% which indicated that the patient was satisfied, and the mean score for reliability was 80.5% which indicated that the patient was satisfied, the mean score for empathy is 84% ​​which indicates that the patient is satisfied, the mean score for direct evidence is 72%, which indicates that the patient is very satisfied. It can be concluded that the average value is 78.1%. This shows that in this study the level of patient satisfaction with drug information services at the Doa Bunda Sentani Pharmacy, Jayapura Regency, was in the satisfied category.